2009
DOI: 10.1590/s1516-44462009000100009
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and reliability of the elderly version of the Camberwell Assessment of Needs (CANE): results from the São Paulo Ageing & Health Study

Abstract: The Brazilian version of the Camberwell Assessment of Needs for the Elderly Scale is a feasible, reliable and, to the extent assessed, valid assessment of unmet needs in a disadvantaged low and middle income countries setting. Its practical utility as a clinical tool remains to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 10 publications
3
12
0
1
Order By: Relevance
“…Stimulation of the brain by non-invasive technique such as tDCS, regulates the function of non-specific neural structures, and improves corticomotor excitability and motor function enhancement14 ) . tDCS is a comfortable and painless corticomotor stimulation technique that induces functional changes dependent on the parameters, intensity, duration, and location of stimulation9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of the brain by non-invasive technique such as tDCS, regulates the function of non-specific neural structures, and improves corticomotor excitability and motor function enhancement14 ) . tDCS is a comfortable and painless corticomotor stimulation technique that induces functional changes dependent on the parameters, intensity, duration, and location of stimulation9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The CANE allows the collection of information on met and unmet needs of older individuals from different perspectives, including the individual himself/herself, relatives, and caregivers or health care professionals. Recent studies showed that the CANE can be used as a reliable and valid need assessment in a broad range of settings [19,24,27,28,29]. Respectable evidence for reliability and validity was also found for the German-language version of the CANE [30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Other factors that could have influenced the results are the timing of the research during a period of political instability and the geographic location of the study, an area with strong affiliations to parties in the conflict, and known for its rural exodus. Given the circumstances, it was not possible to repeat interviews in order to assess the inter-rater and test-retest reliability of the questionnaire, as has been successfully done in other community studies (Fernandes & Gonc¸alves-Pereira, 2009;Mesa et al, 2002;Sousa et al, 2009;van der Roest et al, 2008). Finally, the responses to questions on alcohol consumption, mental health, abuse and psychotic symptoms should be treated cautiously: alcohol consumption is considered by many to be against Islamic strictures, and abuse and psychiatric disturbance are largely unrecognized and/or stigmatized.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of multiple perspectives is one of the strengths of the tool, as this helps to give a more balanced view of a particular person's situation and reduces bias (Martin & Martin, 2003). The CANE has also been used in primary care and community settings, where the data has been collected from the older person only in a single assessment process or from older persons and their informal carers/family members (Mateos, Ybarzabal, Garcia, Amboage, & Fraguela, 2004;Mesa, Mateos Alvarez, Garcia Alvarez, Amboage, & Fraguela, 2002;Smith & Orrell, 2007;Sousa, Scazufca, Menezes, Crepaldi, & Prince, 2009;van der Roest, Meiland, van Hout, Jonker, & Dro¨es, 2008;Walters, Iliffe, & Orrell, 2001). Researchers in the Brazil study have suggested that the CANE may be a promising tool to use in community settings in developing countries (Sousa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%